SPECIFIC FEATURES OF THE PERCEPTIONAL PROCESS IN SPEECH DISORDERS (International journal of artificial intelligence, 2026)
this in the article The specific features of the cognitive process in speechdisorders and the correctional and speech therapy at work speech disadvantages correctionwith together perception development is also required to be done revealed